2014
DOI: 10.1039/c4ra05209a
|View full text |Cite
|
Sign up to set email alerts
|

Prussian blue nanoparticles for laser-induced photothermal therapy of tumors

Abstract: We describe Prussian blue nanoparticles (PB NPs) for laser-induced photothermal therapy (PTT) of tumors. The PB NPs exhibit strong absorbance at near infrared (NIR) wavelengths, are stable, non-toxic, and have 20.5% photothermal conversion efficiencies. PTT with PB NPs in a mouse model of neuroblastoma resulted in marked tumor debulking, increased tumor-free days, and decreased tumor growth rates in tumor-bearing mice. These findings demonstrate the clinical potential of PB NPs for PTT of tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
92
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 34 publications
7
92
1
1
Order By: Relevance
“…Additionally, the nanoparticles retained their photothermal heating properties over four cycles of heating and cooling ( Figure 4C) indicating their stability as photothermal agents over multiple heating cycles. Finally, studies conducted to calculate the photothermal conversion efficiency ( Figure 4D) demonstrated that the nanoparticles had a photothermal conversion efficiency of 16.1%, which is consistent with the previously determined photothermal conversion efficiency of Prussian blue nanoparticles (around 20%) 35 despite others). 32,38,39 Similarly, T2W scans demonstrated that the Fe 3 O 4 @GdPB nanoparticles generated increased contrast in a concentration-dependent manner ( Figure 3B), ie, increased darkening with increasing concentrations, similar to Fe 3 O 4 nanoparticles, which have been well-described in the literature.…”
Section: Fe 3 O 4 @Gdpb Nanoparticles Function As Effective Ptt Agentssupporting
confidence: 66%
See 3 more Smart Citations
“…Additionally, the nanoparticles retained their photothermal heating properties over four cycles of heating and cooling ( Figure 4C) indicating their stability as photothermal agents over multiple heating cycles. Finally, studies conducted to calculate the photothermal conversion efficiency ( Figure 4D) demonstrated that the nanoparticles had a photothermal conversion efficiency of 16.1%, which is consistent with the previously determined photothermal conversion efficiency of Prussian blue nanoparticles (around 20%) 35 despite others). 32,38,39 Similarly, T2W scans demonstrated that the Fe 3 O 4 @GdPB nanoparticles generated increased contrast in a concentration-dependent manner ( Figure 3B), ie, increased darkening with increasing concentrations, similar to Fe 3 O 4 nanoparticles, which have been well-described in the literature.…”
Section: Fe 3 O 4 @Gdpb Nanoparticles Function As Effective Ptt Agentssupporting
confidence: 66%
“…35 The PTT capabilities of the Where h is the heat transfer coefficient, A is the surface area of heat transfer of the system, T max is the maximum system temperature, T amb is the ambient temperature, Q 0 is the rate of heat input due to absorption of light energy by water, I is the incident laser power, and A λ is the absorbance of the Fe 3 O 4 @GdPB at 808 nm.…”
Section: Photothermal Properties Of the Fe 3 O 4 @ Gdpb Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…PB and its analogues possess magnetic properties, so PB nanoparticles can act as an MRI contrast agent [16]. In addition, recently PB nanoparticles have also emerged as a new generation of photothermal agent owing to its high absorption in the NIR spectrum [17,18]. Since then, several theranostic nanoparticles have been developed using PB nanoparticles.…”
Section: Introductionmentioning
confidence: 99%